2016
DOI: 10.1021/acsami.6b05697
|View full text |Cite
|
Sign up to set email alerts
|

Liquid PEG Polymers Containing Antioxidants: A Versatile Platform for Studying Oxygen-Sensitive Photochemical Processes

Abstract: This article proposes the exploitation of widely available, inexpensive, innocuous "green" liquid polyethylene glycol (PEG) polymers containing the oxygen scavenger oleic acid (OA) as promising media for studying oxygen-sensitive photochemical processes. Here we report the successful application of this media to detailed investigations of triplet-sensitized photochemical upconversion, previously established as being readily poisoned by dissolved oxygen. Three different PEG materials were investigated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…Oxygen was consumed only very slowly in the dark, but was fully depleted after 5 min of red light irradiation. These results confirm that the antioxidant scavenges the singlet-oxygen that is generated by the photosensitizer upon irradiation [25,34]. When the experiment was repeated in presence of 0.25-50 mM L-Asc or 1-20 mM GSH, i.e., close to the biological concentrations of these two species [41], the "lag time" before upconversion progressively decreased with increasing antioxidant concentration to as low as 0.5 min lag time at 50 mM of L-Asc ( Figure S2).…”
Section: Anti-oxidants Allow Efficient and Stable Tta-uc In Air With supporting
confidence: 72%
See 1 more Smart Citation
“…Oxygen was consumed only very slowly in the dark, but was fully depleted after 5 min of red light irradiation. These results confirm that the antioxidant scavenges the singlet-oxygen that is generated by the photosensitizer upon irradiation [25,34]. When the experiment was repeated in presence of 0.25-50 mM L-Asc or 1-20 mM GSH, i.e., close to the biological concentrations of these two species [41], the "lag time" before upconversion progressively decreased with increasing antioxidant concentration to as low as 0.5 min lag time at 50 mM of L-Asc ( Figure S2).…”
Section: Anti-oxidants Allow Efficient and Stable Tta-uc In Air With supporting
confidence: 72%
“…To solve this issue, we and others recently showed that antioxidants such as L-histidine, ascorbic acid, or glutathione, can protect TTA-UC against oxygen: upon irradiation of TTA-UC vesicles in air, the photosensitizer initially generates singlet oxygen, which is scavenged by the antioxidant until all oxygen in the irradiated volume has been consumed ( Figure 1b) [25,[34][35][36][37]. Once the O 2 concentration reaches a certain threshold, TTA-UC switches on and remains stable for minutes to even hours in spite of the air atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…DPA/PdOEP: 18% in toluene, [30] DPA/PtOEP: >23% in ethanol or tetrahydrofuran, [3,28,31] perylene/PdTPBP: 38% in tetrahydrofuran), [32] whereas microemulsions (e.g. DNAMe/PdMeTPP: 16%, oil-in-water) [16,33] or more sophisticated mixtures [13,34] have been proposed for efficient upconversion under ambient conditions. Suspensions of nanoparticulate [35][36][37][38] or encapsulated systems [39][40][41][42] and some organic solutions [8,16] display good but usually lower TTA-UC efficiencies when operated under ambient conditions.…”
Section: Main Textmentioning
confidence: 99%
“…Taken together, these results highlight that the glassy polymer matrix protects the liquid nanophase surprisingly well from atmospheric oxygen and that the use of a volatile liquid component is no fundamental obstacle for longevity, although the stability needs to be clearly improved before technological exploitation in devices is feasible. Strategies to achieve this include the use of dyes with better (photo)stability (DPA is well-known undergo (photo)oxidation to an endoperoxide and dimerize, respectively, [2,49,50] ), the addition of stabilizers, [34,51,52] a less volatile solvent, [53,54] and perhaps additional barrier layers. [7] The fact that the upconversion observed in the dye doped nanodroplet-containing polymer is the result of TTA-UC was confirmed by time-resolved PL measurements (inset of Figure 3d).…”
Section: Main Textmentioning
confidence: 99%
“…In other words, the upconverting drug carrier did not function in oxygen-rich conditions, and the use of such systems in vivo would lead to unreliable performance, because oxygen concentrations vary drastically in biological tissues. 3638 The oxygen sensitivity of TTA-UC can be reduced by developing upconversion systems that either (i) feature very fast TTA-UC so that upconversion takes place faster than physical quenching by molecular oxygen, 7,17 (ii) have built-in chemical agents that consume molecular oxygen, 8,3941 or (iii) are protected by a physical barrier that cannot be crossed by molecular oxygen. Most noteworthy examples of the latter strategy include upconverting oil-core nanocapsules embedded in an oxygen protective cellulose material or poly(vinyl alcohol) nanofibers, 19,42 and upconversion in hyperbrached unsaturated polyphosphoesters.…”
Section: Introductionmentioning
confidence: 99%